1993
DOI: 10.1021/j100141a029
|View full text |Cite
|
Sign up to set email alerts
|

SFG study of two-dimensional orientation of surface methyl groups on cadmium arachidate Langmuir-Blodgett films

Abstract: The orientational order of the methyl groups on the surface of cadmium arachidate Langmuir-Blodgett (LB) films with a various number of accumulated monolayers on fused silica has been studied by infrared-visible sum frequency generation (SFG) and Fourier transform infrared absorption (FTIR) spectroscopies. An analysis has been made of the significant in-plane anisotropy of the SFG signals observed for multilayered films and of the change in peak intensities as a function of the number of layers using previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 17 publications
4
52
2
Order By: Relevance
“…For an isotropic surface, p-polarized infrared and s-polarized visible beams necessarily produce an s-polarized signal. 5,[25][26][27][28] With these polarizations, Eq. ͑1͒ becomes…”
Section: ͑1͒mentioning
confidence: 99%
“…For an isotropic surface, p-polarized infrared and s-polarized visible beams necessarily produce an s-polarized signal. 5,[25][26][27][28] With these polarizations, Eq. ͑1͒ becomes…”
Section: ͑1͒mentioning
confidence: 99%
“…The theory behind SFG as a surface-sensitive spectroscopic technique and the analysis to obtain orientation of methyl and methylene groups has been discussed previously. [12][13][14][15][16][17][18][19] Here we summarize the main points to understand the work reported in this paper. The second-order nonlinear susceptibility can be expressed using a Lorentzian function with a resonance peak at ω q and width Γ q corresponding to a resonance mode q.…”
mentioning
confidence: 96%
“…There have been concerns that the possible rotation around sp 3 hybridized C-C sigma bonds would invalidate the analysis model being proposed. It is worth noting that the tight packing of the non-ionic MIBC molecules at the air/water interface would minimize such rotation, which has been observed with dodecanol and phospholipids [6,[19][20][21]28]. Furthermore, molecular mechanics calculations suggested that the probability of gauche conformation was only 1.5% (see further details in SI); it is thus a valid assumption that the C-C rotation is minimal.…”
Section: Theoretical Modellingmentioning
confidence: 89%
“…(5) can be probed by the symmetric C-H stretching mode t s while the anti-symmetric (degenerate) CH stretching mode can be described by the elements in Eqs. (6, 7) [19,20]. Furthermore, Eq.…”
Section: Theoretical Modellingmentioning
confidence: 98%